The Tradition of Bilang Mule in Determining the Beginning of the Month of Ramadan from a Islamic Legal Perspective - Sri Ujiana Putri; Munira, Munira; Siti Suarni, Siti Suarni (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2024)
This study aims to find out how the determination of the beginning of the month of Ramadan in Islam and the review of Islamic law on the Bilang Mule Tradition in determining the beginning of the month of Ramadan is a case study in Badak Village, Central Aceh. The problems raised in this study are; First, how to determine the beginning of the month of Ramadan in Islam in Badak village, Central Aceh. Second, what is the Islamic view regarding the mule word in determining the beginning of the month of Ramadan in Badak Aceh Tengah village. In an effort to obtain answers to the problems, the researchers used a type of field descriptive research, using a normative, historical, and phenomenological approach. The research results found are; First, the determination of the beginning of the month of Ramadan from the perspective of Tengku Samin as the Chief Imam in Badak village, Central Aceh is carried out by the reckoning method in the form of a count of five method, the count of five method is included in the reckoning method because in the daily market it follows the concept of urfi reckoning. Second, the Islamic view regarding saying mule in determining the beginning of the month of Ramadan is not permissible because there is no similarity in how to follow the rukyatul hilal and reckoning.